Size structure of the coral Stylophora pistillata across reef flat zones in the central Red Sea - Walter A. Rich; Susana Carvalho; Ronald Cadiz; Gloria Gil; Karla Gonzalez; Michael L. Berumen (Scientific Reports, 2022)
Abstract Demographic analyses offer insight into the state of a population. Here, we surveyed different reef flat zones (exposed, midreef and sheltered) of six reefs over a cross-shelf gradient to characterize the population structure of Stylophora pistillata, a coral species which dominates reef flats in the central Red Sea. Phototransects were conducted at each reef flat zone, and the density of S. pistillata, the planar area of each colony, and the occurrence of partial mortality were calculated using the program ImageJ. Each colony was also assigned a color morph (yellow, purple or mixed colors). Density and mean size were extremely variable, both among reef flat zones and reefs, but overall, both metrics were lower on the midshelf reefs. The yellow color morph accounted for nearly 90% of colonies surveyed and dominated most reef flats assessed, with the exception of one site where 81% of colonies were purple morphs. There were no spatial trends in the percentage of colonies suffering partial mortality, but overall there is a positive correlation with size class and proportion of colonies with partial mortality. Despite few trends emerging from assessing individual parameters, a PERMANOVA analysis revealed differences among reef flat zones in most of the reefs, highlighting the importance of multivariate analysis. The data presented here serve as a baseline for monitoring and may identify possible future demographic changes to this important coral species in a region increasingly affected by bleaching events.